Effects of levothyroxine treatment on insulin sensitivity, endothelial function and risk factors of atherosclerosis in hypothyroid women - GÖZÜ, HÜLYA (MASSON EDITEUR, 2014)
Objectives. - Contradictory results are encountered in literature regarding the effects of hypothyroidism on the risk factors of atherosclerosis. We aimed to explore the changes in atherosclerotic risk factors and insulin sensitivity before and after levothyroxine replacement therapy in women with primary hypothyroidism and compare with that of healthy controls. Patients and methods. - Twelve patients (mean age of 34 +/- 11.7 years) without an evident disease except for primary hypothyroidism (TSH >= 20 mIU/L) and eleven euthyroid, age-matched (33.8 +/- 8.4 years) female volunteers as controls were included. Baseline thyroid hormones, lipid parameters, homocysteine, fibrinogen levels were measured in both groups. Flow-mediated endothelial-dependent vasodilatation (FMD) method was used to evaluate endothelial dysfunction. Insulin sensitivity was assessed by M values based on euglycemic hyperinsulinemic clamp technique. The same measurements were performed after 6 months of levothyroxine treatment and recovery of euthyroid state in hypothyroid patients. Results. - Treatment reduced total cholesterol (P < 0.005), LDL-cholesterol (P < 0.005), lipoprotein(a) (P < 0.01), fibrinogen (P < 0.0001) and homocysteine (P < 0.0005) levels. Treatment significantly improved M values of hypothyroid patients (3.68 +/- 1.53 mg/kg.min vs 6.02 +/- 1.21 mg/kg.min, P < 0.0001) and FMD (9.1 +/- 3.7% vs 16.4 +/- 4.4%, hypothyroid vs euthyroid, P < 0.0001). Significant correlations were found between M values and TSH (r = -0.6, P < 0.005), fibrinogen (r = -0.53, P < 0.01) measurements, free T3 (r = 0.51, P < 0.02) and free T4 (r = 0.49, P < 0.02) levels. FMD was significantly correlated with fibrinogen levels (r = 0.49, P < 0.05). Conclusion. - Insulin resistance, endothelial dysfunction, atherosclerotic risk markers improves with treatment of hypothyroidism. (C) 2014 Published by Elsevier Masson SAS.
Keywords: Hypothyroidism; Atherosclerosis; Insulin resistance; Endothelial function; CORONARY-ARTERY-DISEASE; SUBCLINICAL HYPOTHYROIDISM; CARDIOVASCULAR RISK; THYROID-FUNCTION; HOMOCYSTEINE; LIPOPROTEIN(A); REPLACEMENT; METABOLISM; DYSFUNCTION; RESISTANCE